Analisis Dampak Co-creation Experience Dalam Perkembangan Bisnis Pariwisata Kota Medan di Era Digital Saat Ini - Andriani Safirah; Shella Angelika Gea; Hanna Banjarnahor; Yasser Muda Panjaitan; Yohannes Sinaga; Onan Marakali Siregar; Afrila Mulyati Siregar (CV. ITTC INDONESIA, 2024)
The field of tourism in Medan city is an interesting research object to study due to the influence of technology in the current digital era. In the midst of the development of information and communication technology, the role of co-creation experience has been found to be one of the important factors to increase the attractiveness of tourism in a region. This research aims to analyze the impact of Experience Co-creation in business tourism development in the current digital era. today's digital era. This research uses a qualitative method research method. Data collection techniques about business development in the current digital era, through online surveys, Google form or directly by giving questions to several customers and observing social media to collect information about digital business. The results of this study from 10 journals and 35 respondent obtained that there are impacts of co-creation experience in business development in the current digital era where businesses such as the tourism sector become businesses that are affected by Co-creation Experience. In addition, social media was also found to be an effective means of interaction with customers so as to create Co-creation Experience for existing human resources, such as tourists. such as travelers. Individual usage experience, product community brand, usage experience, and collective experience emphasize the importance of the brand strategy to engage social members to stimulate Co-creation Experience.